Evaluation of different decontamination procedures on bond strength to sound and caries affected dentin using "no-wait" universal adhesive - Lamiaa M Moharam; Haidy N Salem; Sherif Khadr; Ahmed Abdou (BMC, 2023)
Abstract Background Current study aimed to evaluate the effect of different decontamination procedures on micro-shear bond strength (μSBS) of sound (SoD) and caries-affected dentin (CAD) of two universal adhesives after blood-saliva contamination. Methods One hundred and eighty bovine anterior teeth were prepared and allocated into the respective groups according to tested dentin substrates [SoD, CAD], universal adhesives [Clearfil Bond Universal Quick (UBQ), All-Bond-Universal (ABU)], adhesive contamination stage [none, contamination before and after adhesives light-curing], and according to decontamination procedures [no decontamination, water rinsing, adhesive rebond, Ethylenediaminetetraacetic acid (ETDA) and chlorhexidine (CHX) application]. Universal adhesives were applied according to manufacturer instructions in self-etch (SE) bonding mode. Four composite microrods were built for each tooth. Specimens were kept in distilled water for 24 hours at 37°C before testing μSBS. Four-way ANOVA and Tukey HSD tests were used for data analysis. Results A statistically significant difference between contamination stages of both universal adhesives at different decontamination procedures for SoD and CAD. Highest μSBS was recorded for UBQ control group at SoD, while the least was recorded for light-cured ABU upon water rinsing decontamination procedure of CAD. Conclusions Proper cavity isolation is mandatory to avoid possible contamination which can dramatically affect μSBS. CHX is a potent cavity decontaminant that can restore different dentin substrates bond strength. EDTA presents a promising substitute. UBQ adhesive showed better bonding performance than ABU to both dentin substrates. Application of regular cavity decontamination approaches is highly advised in daily practice to avoid possible detrimental effect of accidental cavity contamination.